(untitled) - Kearney, Hugh F. (Cambridge,New York, 1989)
This is a unique account of the British Isles from pre-Roman times to the twentieth century, distinguished by its stress on the fact that English history forms only part of a wider "history of four nations." To ignore this wider dimension is to distort our view of the past and hinder our understanding of the present. Wide-ranging, the book transforms and challenges traditional accounts of what constitutes national history
Keywords: Great Britain,Ireland,Lịch sử Anh,Lịch sử Ailen; History,History